Effect of vibratory stimulation on pain during local anesthesia injections: a clinical trial - Sajedeh Ghorbanzadeh; Hoda Alimadadi; Nazanin Zargar; Omid Dianat (Restorative Dentistry & Endodontics)
ObjectivesThis study aimed to assess the effect of DentalVibe on the level of pain experienced during anesthetic injections using 2 different techniques.Materials and MethodsThis randomized crossover clinical trial evaluated 60 patients who required 2-session endodontic treatment. Labial infiltration (LI) anesthesia was administered in the anterior maxilla of 30 patients, while inferior alveolar nerve block (IANB) was performed in the remaining 30 patients. 1.8 mL of 2% lidocaine was injected at a rate of 1 mL/min using a 27-gauge needle. DentalVibe was randomly assigned to either the first or second injection session. A visual analog scale was used to determine participants' pain level during needle insertion and the anesthetic injection. The paired t-test was applied to assess the efficacy of DentalVibe for pain reduction.ResultsIn LI anesthesia, the pain level was 12.0 ± 15.5 and 38.1 ± 21.0 during needle insertion and 19.1 ± 16.1 and 48.9 ± 24.6 during the anesthetic injection using DentalVibe and the conventional method, respectively. In IANB, the pain level was 14.1 ± 15.9 and 35.1 ± 20.8 during needle insertion and 17.3 ± 14.2 and 39.5 ± 20.8 during the anesthetic injection using DentalVibe and the conventional method, respectively. DentalVibe significantly decreased the level of pain experienced during needle insertion and the anesthetic injection in anterior LI and mandibular IANB anesthesia.ConclusionsThe results suggest that DentalVibe can be used to reduce the level of pain experienced by adult patients during needle insertion and anesthetic injection.